Pelatihan Pemanfaatan Program Analisis Sosiometri dalam Pelayanan Bimbingan dan Konseling bagi Konselor - Yusri Yusri; Frischa Meivilona Yendi (Jurnal Aplikasi IPTEK Indonesia, 2017)
To improve the educational  quality is an importan  attemp that should be done by all Indonesian and government. The bundles of educational  problems have to be solved and distributed not only to the municipal  government but also to the prefectural  government and  the  stakeholders  of education.  The  distribution  of task  and  responbility  on  the improvement of educational  quality cannot be done automatically  without stakeholders’ comprehension  and understanding  of the importance  of educational  improvement. But, teachers  and  school  principal  at least  can  do much when the stakeholdersgive  much attention and prosperity to make them better life and more professional. In addition, the concept of school based management should be implemented soon to support the decentralization of educational  management.  It hopefully could  make more  effective beurocracy.   However,  it  has  to  be  implement  wisely and  carefully  to  avoid  wider corruption,  collusion, and nepotism at the local and root level